Pomen uzaveščanja narečnega besedja pri učečih se - Valh Lopert, Alenka (Revija za elementarno izobraževanje, 2021)
The Importance of Dialect Awareness among Learners. The Dictionary of Standard Slovenian Language (SSKJ 2014) uses seven types of labels (qualifiers). The present article focuses on the style-genre label nar.(dialectal), further specified as vzhodno (eastern). There are 414 entries so labelled in the SSKJ2. This survey will focus on verbs only (98), labelled as dialectal eastern in the SSKJ2, comparing them to those found in Rajh’s material for his dialectal dictionary of Prlekija dialect Gúčati po antùjoško (2010), as well as in The Slovenian Orthography (Slovenski pravopis – SP 2001). The aim is to point out the importance of incorporating the current dialectal vocabulary into the normative manuals, as well as the importance of their labelling being a great help for teachers, language editors, translators, etc.
Keywords: Slovenian language, dialect, dictionary labels, eastern dialect, verb, The Dictionary of Standard Slovenian Language2, The Slovenian Orthography, Gúčati po antùjoško; Gúčati po antùjoško; Slovenian language; dialect; dictionary labels; eastern dialect; verb; The Dictionary of Standard Slovenian language; Slovenian Orthography